Communication in Handball Training and Performance, a Lost Variable: Systematic Review (2013-2023); [la Comunicación en la Formación y el Rendimiento del Balonmano. Una Variable Perdida: Revisión Sistemática (2013-2023)] - Espoz-Lazo, S (Campus EDUCA SPORTIS S.L., 2024)
Handball, a highly dynamic and competitive sport, involves a complex interplay of variables influencing player and team performance, with communication being one of them. This article focuses on examining the relationship between communication and coaching in handball during the period 2013-2023. The objective of this systematic review is to unveil the current state of research in this field. Twelve studies were thoroughly reviewed, addressing communication, performance, and coaching in the context of handball through a systematic review following PRISMA guidelines, gathering evidence from an extensive literature search in the Web of Science, covering articles published between 2013 and 2023. The results highlight a growing interest in coach-player communication, particularly aimed at enhancing player performance. The literature underscores the importance of effective communication in training and performance but identifies a lack of a comprehensive approach to communication as a critical variable. Despite ample evidence of its significance, the exploration of communication in the context of handball is still in its early stages compared to other sports. It is concluded that there is a rising interest in the relationship between coach communication and player performance in handball, but a more comprehensive approach is needed. Coaches can use this information to enhance training and performance. © 2024, Campus EDUCA SPORTIS S.L.. All rights reserved.